Numerical study on wavy interfaces - Tham, Yong Kin (2019)
The interface between two solids is normally non-flat. The waviness of the interface introduces some new mechanical behaviours. In the present project, a numerical analysis via finite element method (FEM) is employed on the micro and macro models to study the elastic stiffness of the wavy interface with the application of finite element software, ANSYS. Following, the effective stiffness through the wavy interface is acquired and analysed through comparison of both simulated models. Various boundary conditions and methods of analysis are utilised in this paper. It is observed that the presence of waviness of the interface causes a decrease in effective stiffness of the interface which complies with past researches. In addition, a decrease in effective stiffness would result in an increase in bond weakening of materials at an interface